Prostate cancer aggressiveness and age: Impact of p53, BCL-2 and microvessel density. (December 2018) - Calvocoressi, Lisa; Uchio, Edward; Ko, John; Radhakrishnan, Krishnan; Aslan, Mihaela; Concato, John
Older men are more likely to have advanced prostate cancer at time of their diagnosis, but whether prostate tumors are inherently (biologically) more aggressive with advancing age is uncertain. To address this gap in knowledge, we analyzed data from veterans (n=971) diagnosed with prostate cancer during 1991–1995. Factors included age, detection of prostate cancer by screening, prostate-specific antigen (PSA) level, anatomic stage, and Gleason score. Information on molecular markers obtained from immunohistochemical staining of prostate tissue, included B cell lymphoma-2 (bcl-2), p53, and microvessel density (MVD), each having a previously documented association with disease progression and increased risk of prostate cancer death. We first examined the bivariate association of demographic, clinical, and molecular factors with age, and found evidence that race, screening status, Gleason score, PSA, bcl-2, p53, and MVD varied across categories of age in this study population. After further characterizing the association between age and Gleason score, we used logistic regression to examine the association between age and molecular markers—accounting for race, screening status, PSA, and Gleason score. Comparing men older than 80 years to those younger than 70 years, adjusted ORs and 95% CIs were 1.89 (0.73 to 4.92), 1.91 (1.05 to 3.46), and 2.00 (1.06 to 3.78), for positive bcl-2, p53, and MVD markers, respectively; no statistically significant associations were found for men 70–79 years old, compared with men younger than 70 years. These novel findings suggest that very elderly men often present with biologically aggressive prostate cancer; the results also have potential implications for therapeutic decision-making.